Degree of Approximation of Functions f(x,y) by Double Hausdorff Matrix Summability Method - Mishra, Abhishek; Mishra, Vishnu Narayan (Discontinuity, Nonlinearity, and Complexity, 2026)
The degree of trigonometric approximation of periodic functions f(x,y) belonging to generalized Hölder class by double Hausdorff matrix summability means of double Fourier series has been obtained in this paper. Some corollaries have also been established to find estimates of approximation using almost Euler means and (C, γ, δ ) means.